Pedestrian modern : shopping and American architecture, 1925-1956 - Smiley, David J. (University of Minnesota Press, 2013)
'Pedestrian Modern' shows that stores and shopping centres were integral to the shaping of modernism in the middle decades of the 20th century. Rather than framing store work as some parallel or lesser realm of architectural work tied only to consumption or suburbanisation, as is the typical view, this book shows that store and shopping centre design work were described as uniquely fitting for the emerging tenets of modernist architecture.